Обвинувачення в кримінальному процесі України - Слінько, С. В.; Slinko, S. V. (Європейські перспективи. - 2024. - № 2. - С. 59-64, 2024)
Визначено процесуальна сутність обвинувачення, на початку досудового розслідування, під час оголошення повідомлення про підозру, обрання міри запобіжного заходу та визнання обвинуваченого винним і проголошення вироку. На підставі нормативного визначення положень чинного законодавства та елементів застосування практики розроблено положення щодо поняття, предмета, змісту, процесуальної форми обвинувачення. Запропоновано класифікаційні ознаки сторони обвинувачення на стадіях, окремих етапах процесу.

Theoretical aspects of prosecution and criminal prosecution have been constantly emphasized in scientific publications. Scientists did not have a single theoretical approach to the definition of prosecution. Criminal prosecution has always caused controversy in academic circles. On the one hand, the current criminal procedural code determined the content of the indictment, on the other hand, the legislation excludes the status of the accused at the stage of pre-trial investigation, and establishes it only at the stage of trial. The problem of criminal prosecution is solved by law. The main elements are established during the pre-trial investigation in the case of searches, operative searches, searches for the suspect. The stage of the trial is established on the basis of the adversarial nature of the parties, the participants in the process, therefore criminal prosecution has no legal basis for its application. Based on the analysis of scientific points of view, a classification of the main provisions of the accusation and criminal prosecution is provided, the legal and procedural content of these categories is revealed.

Определена процессуальная сущность обвинения, в начале досудебного расследования, при оглашении сообщения о подозрении, избрании меры пресечения и признании обвиняемого виновным и оглашении приговора. На основании нормативного определения положений действующего законодательства и элементов применения практики разработаны положения о понятии, предмете, содержании, процессуальной форме обвинения. Предложены классификационные признаки стороны обвинения на стадиях, на отдельных этапах процесса.
Accusation in the criminal process of Ukraine
Keywords: досудове розслідування; слідчий; прокурор; суддя; обвинувачення; кримінальне переслідування; сторони; учасники; стадія; вирок; pre-trial investigation; investigator; prosecutor; judge; indictment; criminal prosecution; parties; participants; stage; sentence; досудебное расследование; следователь; судья; обвинение; уголовное преследование; стороны; участники; стадия; приговор